2013
DOI: 10.1074/jbc.m112.424150
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Subtype 1 Influenza Neuraminidase Is Driven by Both the Transmembrane and Head Domains

Abstract: Background: Influenza neuraminidase is thought to function as a tetramer, but what drives tetramerization is unknown. Results: The neuraminidase transmembrane domain (TMD) contributes to the assembly process by tethering the stalk to the membrane in a tetrameric conformation. Conclusion:The enzymatic head and TMD coordinate the proper assembly of neuraminidase. Significance: Single-spanning TMDs can contribute to the assembly of distal domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 49 publications
(46 reference statements)
1
61
0
Order By: Relevance
“…This domain forms a nearly parallel four-helix bundle which probably better mimics oligomerization driven by the TMD and which suffices to overcome the oligomerization defect in the VN head domain. These results are in agreement with previous studies that showed the importance of the TMD for folding and assembly of the NA head domain (20,21).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This domain forms a nearly parallel four-helix bundle which probably better mimics oligomerization driven by the TMD and which suffices to overcome the oligomerization defect in the VN head domain. These results are in agreement with previous studies that showed the importance of the TMD for folding and assembly of the NA head domain (20,21).…”
Section: Discussionsupporting
confidence: 83%
“…To test this hypothesis, we expressed the HN and VN head domains in the absence of the artificial tetramerization domain. In addition, the stalk domain was deleted as it was previously shown that removal of the NA stalk domain restores NA activity in the absence of the TMD and an artificial tetramerization domain (20). Removal of the stalk domain from the GCN4-pLI-extended NA proteins (GCN4-NA head ) had a small negative effect for the HN protein but clearly increased the activity of the VN protein (Fig.…”
Section: Construction and Expression Of Recombinant Na Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A [a and e are the polar faces of the TMD model]) (20,21). Contradictory to the need to conserve hydrophobicity for membrane integration, our analysis of the N1 TMDs in human IAVs showed that they have become increasingly more polar since 1918, which results in a stronger TMD association (21).…”
mentioning
confidence: 99%
“…In this construct, the a face Asn residues at positions 21 and 28 in the pN1 TMD were mutated to Ala to produce the pN1 TMD⌬A chimera. For individual analysis, full-length NA (from WSN) and the pN1 TMD and pN1 TMD⌬A chimeras were fused to the C-terminal Myc-His tag in the mammalian expression vector pcDNA3.1A-Myc-His (Invitrogen) by PCR overlap cloning as previously described (20). The pBLM plasmids, used for TMD interaction studies, containing the NA TMDs are previously described (21).…”
Section: Plasmidsmentioning
confidence: 99%